KONSERVATISME AUDITOR PADA OPINI KELANGSUNGAN HIDUP DENGAN MODERASI MANAJEMEN LABA: AUDITOR CONSERVATISM ON GOING OPINION WITH MODERATING EARNINGS MANAGEMENT - Vina, Vina; Harsono, Budi (Universitas Riau, 2023)
The purpose of this research is to find out whether auditor conservatism influences the view of business continuity trading on the Indonesia Stock Exchange. Company profiles on www.idx.co.id, the website of the Indonesia Stock Exchange, were analyzed for 2017 to 2021. In this study data analysis approach, panel data regression and logistic regression are applied, and the outcomes of the sample findings that have been chosen are a total of 1,875. The research findings are certainly able to state that auditor conservatism has a significant effect on earnings management. These results are certainly able to state that auditor conservatism moderated by earnings management has a significant effect on going concern opinion.